Gender inequality, endogenous cultural norms and economic development - Hiller, Victor (Paris, 2008)
"This research focuses on the role played by cultural norms in the long run persistence of gender inequalities. Cultural norms about gender roles are considered to be endogenous and can generate gender inequality and low development traps. Indeed, when the gender gap is internalized, it leads to inegalitarian views about gender roles. Due to these inegalitarian beliefs, boys receive more education and the initial gender gap is reinforced. The existence of gender inequality traps is pointed out by the World Bank as a major obstacle for economic development (WDR 2006). The present article allows for a better understanding of the persistence of such traps and the means to escape. "